Model Analysis of the Mediation Effect of Customer Satisfaction on Customer Loyalty in Mitratel Companies: The Role of CRM and Company Reputation as Predictors - Sugiat, Maria; Sudirman, Acai (Fakultas Ekonomi dan Bisnis, Telkom University., 2024)
The rapid growth of tower assets among Indonesia's three main tower providers shows the increasingly tight competition within the telecommunications business. Therefore, this research analyzed the mediating effect of customer satisfaction on customer loyalty with customer relationship management (CRM) and company reputation as predictors using data from customer satisfaction research conducted with Mitratel clients. The data collected comprised 155 current and former customers of the Mitratel Tower company, collected from survey responses. The data was qualitatively evaluated and analyzed statistically using data processing techniques applied in the SEM-PLS analysis procedure. The result showed that CRM and company reputation directly impact customer satisfaction and loyalty. However, the impact of CRM on loyalty cannot be influenced directly due to the complexity of factors affecting customer loyalty. While customer satisfaction is important in building loyalty, other factors such as price, service quality, brand reputation, and psychological factors also play a significant role. This research provides in-depth insight into how factors such as customer satisfaction, CRM, and company reputation interact to influence customer loyalty. It is also an important basis for Mitratel Companies to design more effective policies and strategies to improve business performance and maintain market share. Keywords—CRM; Company Reputation; Customer Satisfaction; Customer Loyalty